POTENSI MAKANAN TRADISIONAL BALI YANG BERBASIS MASYARAKAT SEBAGAI DAYA TARIK WISATA DI PASAR UMUM GIANYAR - I Nyoman Sunada (JURNAL GASTRONOMI INDONESIA, 2019)
The purpose of this research was to determine the potential of gastronomic,examines the efforts undertaken by the market managers, and to determine the extentof involvement of local community towards the development of Balinese traditionalfood sold at common market of Gianyar. In this research, the data were analyzed withdescriptive qualitative method approach using multiple informants were selectedpurposively and techniques of data collection is done by the method of observation,in-depth interviews and documentation with gastronomic theory and the theory ofproduct development. The results showed that the potential of Balinese traditionalfood gastronomic sold at common market of Gianyar meet the criteria of uniqueness,originalities, authenticity, diversity, as well as an attractive appearance for touristsso decent offer as a tourist attraction. Efforts undertaken by the market managersin the development of Balinese traditional food that sold in the common market ofGianyar is: providing and managing the area for traders, involving the communitiestraditional village of Gianyar to conserve Balinese traditional food heritage, andalways maintain the cleanliness of the market area which impact on the quality ofthe food. Forms of community involvement of the indigenous village of Gianyar inthe development Balinese traditional foods sold at common market of Gianyar is: asthe market manager, as a particular merchant that sells Balinese traditional food, asfood suppliers such as suckling pig (babi guling) and Balinese pastries (jaje Bali)especially visitors who buy Balinese traditional food. Synergy among the traders andmarket management, governments, and local community involvement, in collaborationwith the tourism entrepreneurs was needed to raise the value of Balinese traditionalfood and to achieve the goal of Balinese traditional food development.